Ludzka wolność w ujęciu św. Jana od Krzyża - Rachmajda, Roman Antoni ocd (My University, 2017)
Wolność jest zagadnieniem centralnym w myśli i życiu św. Jana od Krzyża. Dzięki niej można opisać najpełniej to, czym żył i czego nauczał mistyk hiszpański – ścisłą relację, więź, komunię, zjednoczenie z Bogiem, którą określał terminem unión. Rozdział I pracy opisuje statyczne uwarunkowania wolności w systemie świętego, opisane w trzech aspektach: miejsce wolności w jego systemie, w którym centrum stanowi powołanie człowieka do unión miłości z Bogiem, która to unión realizuje się na trzech płaszczyznach: ontycznej, historio-zbawczej i ascetyczno-mistycznej; opis osób stanowiących unión – Boga i człowieka; oraz – sam charakter wolności, jaka istnieje w człowieku zdolnym do unión z Bogiem, i o której święty mówi – wolność wewnętrzna. Rozdziały II i III opisują wymiar realizacji wolności, drogę wyzwolenia u świętego, analizując poznanie w tym procesie. Rozdział II, zatytułowany „Dar i doświadczenie wolności”, to zwykły okres w relacji pomiędzy Bogiem a człowiekiem, którego doświadcza większość ludzi; zawiera on trzy okresy z perspektywy wolności: pierwsze wyzwolenie, noc-wyzwolenie czynne i noc bierną zmysłów. Rozdział II – to czas nie-zwykłej relacji pomiędzy Bogiem a człowiekiem, gdy działa Bóg, stąd „wolność w kręgu Boga”; zaczyna się ona nocą bierną ducha, która prowadzi do unión, w ramach której jest unión/komunia osób i unión/zjednoczenie władz; ta pierwsza jest stała, druga – chwilowa.

Freedom is a the main issue in the thought and life of Saint John of the Cross, by which one can describe as completely as possible what the Spanish mystic lived for and taught – a close relationship, bond, communion, union with God, which he defined as unión. The first chapter of the work describes the static conditions of freedom in the saint’s system, described in three aspects: the place of freedom in the saint’s system, in which the center is the man's calling to the unión of love with God. Furthermore the unión is carried out on three levels: ontical, historio-saving and ascetic-mystical; the description of persons constituting the unión – God and man; and the very nature of the freedom that exists in a man capable of unión with God, and of which the Saint speaks – internal freedom. The next chapters describe the dimension of freedom’s implementation, the path of liberation, analyzing cognition in this process. Furthermore the second chapter: “The gift and experience of freedom”, describes the normal period in the relationship between God and man, which most people experience. It consists of three periods from the perspective of freedom: the first liberation, the active liberation of the night and the passive night of senses. The third chapter deals with the issue of the unusual relationship between God and man, when God acts, hence “Freedom within the circle of God”; it begins at passive night of the spirit, which leads to the unión, within which there is the unión-communion of persons and the unión-unification of the power within it; the first one is constant, the second one is temporary.
St. John's of the Cross human freedom conception
Wydział Teologiczny
Keywords: Bóg; God; człowiek; human; komunia; communion; wolność; freedom; wyzwolenie; liberation